Photodynamic Therapy in Cancer: Insights into Cellular and Molecular Pathways - Vincenzo Papa; Fabiana Furci; Paola Lucia Minciullo; Marco Casciaro; Alessandro Allegra; Sebastiano Gangemi (Current Issues in Molecular Biology, 2025)
Photodynamic therapy is a non-ionizing radiation treatment that utilizes a photosensitizer in combination with light to produce singlet oxygen. This singlet oxygen induces anti-cancer effects by causing apoptotic, necrotic, or autophagic cell death in tumor cells. Currently, photodynamic therapy is employed in oncology to treat various cancers. In the presence of oxygen, this non-invasive approach leads to direct tumor cell death, damage to microvasculature, and the induction of a local inflammatory response. These effects allow photodynamic therapy to be effective in treating early-stage tumors, extending survival in cases where surgery is not feasible, and significantly improving quality of life. In this paper, we provide a state of the art on cytomolecular mechanisms and associated pathways involved in photodynamic therapy. By integrating these mechanistic insights with the most recent advancements in nanotechnology, this phototherapeutic approach has the potential to become a prevalent treatment option within conventional cancer therapies, enhancing its application in precision medicine.